ESP students’ voice: Is Kahoot® helpful to learn English vocabulary during the pandemic? - Mandasari, Yuyun Putri; Wulandari, Eka (LingTera, 2023)
The use of technology is closely linked to the implementation of digital learning. As one of the profiles of the 21st century teachers, digital tools are notably prominent in helping ESP students improve their learning outcome, particularly during the Emergency Remote Learning (ERL) due to COVID-19. Kahoot® as one of the technological advancements in the field of game-based learning was considered to be highly beneficial and helpful for ESP students to be more engaged and motivated in improving their English vocabulary through online means. This study presents ESP students’ perceptions of the use of Kahoot® in an internet-based instruction during the pandemic. Survey research was employed with 51 participating students of the Health Promotion Study Program at Poltekkes Kemenkes Malang. The questionnaire was distributed online with 21 survey items designed to accommodate the students’ points of view. The findings show that the students of the Health Promotion Department had a strong preference to the use of Kahoot® in improving their English vocabulary during the COVID-19 outbreak.